Enhancing consumers' self-reported loyalty intentions in Islamic Banks: The relationship between service quality and the mediating role of customer satisfaction - Ala' Omar Dandis; Len Tiu Wright; Donna Marie Wallace-Williams; Ibrahim Mukattash; Mohammad Al Haj Eid; Huifen Cai (Cogent Business & Management, 2021)
The main objective of this paper is to investigate how service quality and customer satisfaction are correlated to self-reported loyalty intentions in Islamic banks. The paper presents primary data collected by self-administered questionnaires involving a sample of 655 respondents from all local Islamic Banks in Jordan. The results show that compliance, tangibility, responsiveness, assurance, and empathy positively linked to self-reported loyalty intentions, with compliance and assurance appearing as the greatest correlation with self-reported loyalty intentions compared to other service quality dimensions. Islamic banks should focus on continuous improvement of service quality due to the direct correlation with customer satisfaction and loyalty. It is important for Islamic banks to review and endorse all policies and procedures to ensure that their documents and investments are undertaken in line with the requirements of Islamic law. Managers should pay special attention to the service quality provided by their employees and develop their skill set through training and education programmes based on Islamic principles. As the first study of its kind in Jordan, the paper's contribution stems from filling the research gap in examining the relationship between the various service quality dimensions and self-reported loyalty intentions in Islamic banks using the CARTER model.
Keywords: 650; service quality; customer satisfaction; self-reported loyalty intentions; Islamic bank; emerging market; Jordan